THE IMPLEMENTATION OF WRITING PROCESS APPROACH ON WRITING PERSONAL LETTER COMPETENCY OF HOTEL HOSPITALITY STUDENTS IN AKADEMI KOMUNITAS MAPINDO - Safitri, Ni Putu Dianita; Tari, Nirmala; Lindawati, Ni Putu (LITERA : Jurnal Bahasa Dan Sastra, 2020)
ABSTRACTThis classroom action research aims to find out whether or not the implementation ofwriting process approach can improve the hotel hospitality students’ competency in writingpersonal letter. It was conducted after finding out the competency of hotel hospitality studentsin writing personal letter was low. The subjects of the study were 28 hotel hospitality studentsin Akademi Komunitas MAPINDO. The research was done in two cycles consisting ofplanning, action, observation, and reflection in each cycle. The research finding of the studyshowed that writing process approach positively impacts the students’ competency in writingpersonal letter.Keywords: writing process approach, writing competency, personal letterABSTRAKPenelitian tindakan kelas ini bertujuan untuk mengetahui apakah penerapan writingprocess approach dapat meningkatkan kemampuan menulis surat pribadi mahasiswaperhotelan. Penelitian dilakukan setelah mengetahui bahwa kemampuan menulis surat pribadimahasiswa perhotelan masih rendah. Subjek peneletian adalah 28 mahasiswa perhotelan diAkademi Komunitas MAPINDO. Penelitian ini dilaksanakan dalam dua siklus yang terdiri dariperencanaan, tindakan, observasi, dan refleksi di setiap siklusnya. Hasil dari penelitianmenunjukkan bahwa writing process approach memberikan pengaruh positif terhadapkemampuan menulis surat pribadi mahasiswa.Kata Kunci: writing process approach, kemampuan menulis, surat pribadi